Cytotoxicity of the compounds isolated from Pulsatilla chinensis saponins and apoptosis induced by 23-hydroxybetulinic acid. (January 2015) - Liu, Ming; Zhao, Xingzeng; Xiao, Lin; Liu, Ge; Liu, Haizhou; Wang, Xiangyun; Feng, Xu; Lin, Xiukun
Abstract Context: The rizoma of Pulsatilla chinensis (Bunge) Regel has been used as a traditional Chinese medicinal herb for thousands of years. Total saponins from P. chinensis can induce the apoptosis of solid cancer cells; however, their activity on chronic myeloid leukemia and the mechanisms remains unknown. Objective: To study the activity of total saponins and the main active fractions from P. chinensis saponins on chronic myeloid leukemia, and to illustrate the mechanisms underlying the anticancer activities. Materials and methods: The cytotoxic activity were assayed by MTT; cell cycle arrest and apoptosis were tested by flow cytometry system; changes in the mitochondrial membrane potential were determined using JC-1; and the apoptosis signaling pathway was determined by western blotting. Results: We demonstrated that total P. chinensis saponin displayed cytotoxic activity against K562 cell line. In addition, we identified 23-hydroxybetulinic acid (HBA), pulchinenoside A (PA), and anemoside B4 (AB4) from the total saponins, with the most cytotoxic compound HBA. Glycosylation at C3 and C28 of HBA significantly reduces its cytotoxicity. HBA could promote cell cycle arrest at S phase and induce apoptosis via intrinsic pathway. HBA disrupts mitochondrial membrane potential significantly (p < 0.01) and selectively downregulates the levels of Bcl-2, survivin and upregulates Bax, cytochrome C, cleaved caspase-9 and -3. Discussion and conclusion: Total saponins from P. chinensis may be effective natural products against human chronic myelogenous leukemia; HBA is one of the bioactive components responsible for its anticancer activity, and could be further investigated as an alternative therapeutic drug for leukemia.